Applications of snowdrop medicinal plant material in homeopathic pharmacy: a brief historical background and a systematic review of homeopathic medicines standardization - D. O. Bokov; I. A. Samylina (Сеченовский вестник)
Currently, relevant studies are related to the development of private pharmacopeia articles with the requirements for medicinal plant raw materials and homeopathic mother tincture used in homeopathic practice. The article presents a brief overview of the history of the use of snowdrop in the offi cial allopathic and homeopathic medicine. Some aspects of standardization of medicinal plants and tinctures of homoeopathic matrix of Voronov snowdrop (Galanthus woronowii Losinsk) and Galanthus nivalis.